2007
DOI: 10.1007/s00586-007-0409-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity measurement: a new technique to detect iatrogenic initial pedicle perforation

Abstract: Pedicle screw fixation has achieved significant popularity amongst spinal surgeons for both single and multi-level spinal fusion. Misplacement and pedicle cortical violation occurs in over 20% of screw placement and can result in potential complications such as dysthesia, paraparesis or paraplegia. There have been many advances in techniques available for navigating through the pedicle; however, these techniques are not without drawbacks. A new electrical conductivity-measuring device, previously evaluated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…Variation of conductivity occurs when passing between different media, such as exiting the osseous pedicle into surrounding soft-tissue, as occurs during an iatrogenic pedicle perforation. Our series demonstrated a sensitivity of >98% in detecting breaches, more than twice the rate reported by surgeons performing the same surgeries (Bolger et al 2007, Anzhsn 2011.…”
Section: Use Of Pediguard™supporting
confidence: 53%
“…Variation of conductivity occurs when passing between different media, such as exiting the osseous pedicle into surrounding soft-tissue, as occurs during an iatrogenic pedicle perforation. Our series demonstrated a sensitivity of >98% in detecting breaches, more than twice the rate reported by surgeons performing the same surgeries (Bolger et al 2007, Anzhsn 2011.…”
Section: Use Of Pediguard™supporting
confidence: 53%
“…Various techniques are being used to detect pedicle screw misplacement including guide pins into the pedicles, intraoperative C-arm image intensifier; direct visualization of the medial wall after laminotomy, 3D fluoroscopy, CTbased computer assisted navigational systems and advanced intraoperative neurologic monitoring [2,4,11,20,29]. Image-guided techniques result in high cost, expensive equipment and prolonged operating time.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the criticism for the study; however, this is the first study measuring the accuracy and safety of pedicle screw in neuromuscular scoliosis population which might be helpful for future studies. Recently Bogler et al [4] reported that electrical conductivity measuring system using Pediguard may provide a simple, safe and sensitive method of detecting pedicle breeches during the procedure, even with free-hand technique. We also feel that use of this system with free-hand pedicle screw instrumentation would definitely be helpful to surgeons and would increase the accuracy and safety of this procedure (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1,22 Additional methods such as conductivity measurement devices that detect cortical defects have equally proven useful in this respect. 2 Malposition rates with conventional screw placement can be significant. 6 However, the term "malposition" is not well defined and depends on the various grading systems, which are available to evaluate screw position.…”
Section: Advances In Accuracy and Safety Of Pedicle Screw Placementmentioning
confidence: 99%